SCHEMA ACTIVATION IN SHAPING STUDENTS' INTERTEXTUAL RESPONSES IN READING PICTURE BOOK - Dea Rizki Ananda, - (2018)
This research was intended to explain the process of schema activation in shaping students' intertextual responses in reading the selected picture book, My Dad by Anthony Browne. The text is considered as narrative text which is available in the school curriculum. The research was conducted in a high school in Cimahi with 37 students involved as the participants. This research employed a qualitative research design in which the data were collected through classroom observation, students' documents and interview framed within a work by Sipe (2008) that explains types of students' responses of literary text, in particular, intertextual responses. The findings showed that through schema activation, students' intertextual responses and views in reading can be maximized as students' developed intertextual links between the book, other related stories and the students' cultural experiences. The ultimate argument of the paper is that schema activation provides an excellent implication for students' classroom reading activities;---Penelitianinibertujuanuntukmenjelaskan proses aktivasiskemadalammembentukresponintertekstualsiswadalammembacabukubergambar yang telahdipilihyaituMy Dad karya Anthony Browne. Tekstermasukteksnaratif yang terdapatdalamkurikulumsekolah.Penelitianinidilaksanakan di sebuahSekolahMenengahAtas di Cimahidengan 37 siswaterlibatsebagaipesertapenelitian.Penelitianinimengguanakanmetodekualitatifdimana data penelitiandiperolehlewatobservasikelas, dokumensiswadanwawancaradisusundenganmenggunakanteoridariSipe (2008) yang menjelaskanjenis-jenisresponsiswaterhadapkaryasastra, khususnyaresponintertekstual.Hasildaripenelitianinimenunjukanbahwalewataktivasiskema, responintertekstualsiswadanpandangandalammembacadapatdimaksimalkansaatsiswamengembangkanhubunganintertekstualantarabuku, cerita-cerita yang berkaitandanpengalamankulturalsiswa.Argumenutamandaripenelitianiniialahbahwaaktivasiskemamemberikanimplikasi yang sangatbaikbagikegiatanmembacasiswa di kelas.